Nominal group technique and its applications in managing quality in higher education - Abdullah, Muhammad Madi; Islam, Rafikul (Johar Education Society, 2011)
Quality management is an important aspect in all kinds of businesses – manufacturing or service. Idea generation plays a pivotal role in managing quality in organizations. It is the new and innovative ideas which can help orporations to survive in the turbulent business environment. Research in group dynamics has shown that more ideas are generated by individuals working alone but in a group environment than the individuals engaged in a formal group discussion. In Nominal Group Technique (NGT), individuals work alone but in a group setting. This paper shows how NGT can be applied to generate large number of ideas to solve quality related problems specifically in Malaysian higher education setting. The paper also iscusses the details of NGT working procedure and explores the areas of its further applications.